APOE e4 dependent deficits in brain DHA phospholipids and mfsd2a in Alzheimer's disease patients with severe cerebral amyloid angiopathy. (20th December 2022) - Nkiliza, Aurore; Evans, James; Ringland, Charis; Daniel, Niedospial; Huguenard, Claire; David, Roderick; Ojo, Joseph; Crawford, Fiona; Mullan, Michael; Bachmeier, Corbin; Abdullah, Laila
Abstract: Background: The apolipoprotein E e4 allele (APOE4) is a major risk factor, contributing to vascular pathologies in AD which include CAA, BBB dysfunction and reduced cerebral vascular integrity. The diminished capacity of APOE4 to transport docosahexaenoic acid (DHA), an essential fatty acid required for the structural and functional maintenance and vascular integrity of the brain, could also contribute to AD pathogenesis. However, it remains undetermined if changes in the brain DHA content of phospholipids (PL) and DHA transporters exist in relation to APOE4, AD diagnosis and CAA pathology. Method: We performed liquid chromatography/mass spectrometry‐based PL analysis of the cerebrovascular and parenchymal fractions from autopsied human brain of pathologically confirmed AD cases and controls. We performed an antibody‐based examination of the major facilitator superfamily domain containing 2A (mfsd2a) protein in the cerebrovasculature from these subjects and brain homogenates from transgenic mice with human APOE (APOE‐TR) and APOE‐TR crossed with mice with five AD mutations (EFAD). We performed proteomic analyses of the cerebrovascular and parenchymal fractions of the brains from 50‐week‐old APOE‐TR. Result: In the cerebrovasculature and parenchyma, DHA containing PL species were lower in ε4 carriers with AD compared to control ε4 carriers. We observed an ε4‐dependent decrease in mfsd2a level in the cerebrovasculature of ε4 carriers compared to non‐carriers. Stratification of DHA containing PL by CAA showed that these PL levels were reduced in ε4 positive AD patients with severe CAA. In addition, brain levels of DHA containing PC species and mfsd2a were lower in APOE4‐TR and E4FAD mice compared to other genotypes in each mouse model. Furthermore, protein levels of glucose transporter 1 (Glut1) and a metabolite transporter, monocarboxylate transporter 1 (MCT1), were lower in the cerebrovasculature of APOE4‐TR relative to APOE3‐TR and APOE2‐TR mice. Conclusion: These findings demonstrate that brain DHA deficiencies in ε4 carriers may be due to reduced mfsd2a expression and partly associated with severe CAA. Thus, targeting this transport mechanism may improve the bioavailability of DHA into the brains of ε4 carriers who are at risk of developing AD.